Annual dynamics of phosphatase activities in an evergreen oak litter: influence of biotic and abiotic factors - Criquet, S.; Ferré, E.; Farnet, A. M.; Le petit, J. (Soil Biology and Biochemistry, 2004)
As part of a study of the processes involved in litter biodegradation, we considered the variations over 1 year of the phosphatase activities in sclerophyllous evergreen oak litter (Quercus ilex L.). Evergreen oak is representative of tree species in the forests of the French Mediterranean area. Acid (E.C. 3.1.3.2.) and alkaline (E.C. 3.1.3.1.) phosphatases, were measured over 13 months in the forest litter, along with several biotic and abiotic variables, potentially involved in the regulation of these enzymes. These comprised moisture, temperature, pH, water-extractable inorganic P (PI ), fungi, culturable heterotrophic bacteria and protein concentrations. Moisture considerably affected the production of proteins and acid phosphatases, probably formed by litter microorganisms. This result corroborated the study of Criquet et al. [Soil Biology and Biochemistry 34 (2002) 1111] which indicated that rainfall was the most important factor regulating the production and the activity of numerous enzymes in sclerophyllous forest litter. However, it appeared that moisture cannot alone predict all of the variations in phosphatase activities and the mineralisation rate of organic P (PO). Indeed, principal component analyses (PCA) and multiple regressions showed that temperature and bacterial communities were also implicated in phosphatase dynamics and PO mineralisation. Acid phosphatases were negatively correlated with the temperature, whilst alkaline phosphatases were positively correlated with this variable. The signiﬁcant correlation obtained between bacteria and PI concentrations, and the lack of correlation between bacteria and both acid and alkaline phosphomonoesterases, suggest that other important phosphatase types, such as phosphodiesterases, must be strongly implicated in PO mineralisation of the litter and in the regulation of P microbial metabolism.
Keywords: biodegradation; phosphatases; phosphate; phosphomonoesterases; phosphorus transformations; Quercus ilex

Annual dynamics of phosphatase activities in an evergreen oak litter: influence of biotic and abiotic factors - Criquet, S; Ferré, E; Farnet, A M; Le petit, J (Soil Biology and Biochemistry, 2004)
As part of a study of the processes involved in litter biodegradation, we considered the variations over 1 year of the phosphatase activities in sclerophyllous evergreen oak litter (Quercus ilex L.). Evergreen oak is representative of tree species in the forests of the French Mediterranean area. Acid (E.C. 3.1.3.2.) and alkaline (E.C. 3.1.3.1.) phosphatases, were measured over 13 months in the forest litter, along with several biotic and abiotic variables, potentially involved in the regulation of these enzymes. These comprised moisture, temperature, pH, water-extractable inorganic P (PI ), fungi, culturable heterotrophic bacteria and protein concentrations. Moisture considerably affected the production of proteins and acid phosphatases, probably formed by litter microorganisms. This result corroborated the study of Criquet et al. [Soil Biology and Biochemistry 34 (2002) 1111] which indicated that rainfall was the most important factor regulating the production and the activity of numerous enzymes in sclerophyllous forest litter. However, it appeared that moisture cannot alone predict all of the variations in phosphatase activities and the mineralisation rate of organic P (PO). Indeed, principal component analyses (PCA) and multiple regressions showed that temperature and bacterial communities were also implicated in phosphatase dynamics and PO mineralisation. Acid phosphatases were negatively correlated with the temperature, whilst alkaline phosphatases were positively correlated with this variable. The signiﬁcant correlation obtained between bacteria and PI concentrations, and the lack of correlation between bacteria and both acid and alkaline phosphomonoesterases, suggest that other important phosphatase types, such as phosphodiesterases, must be strongly implicated in PO mineralisation of the litter and in the regulation of P microbial metabolism.
Keywords: biodegradation; phosphatases; phosphate; phosphomonoesterases; phosphorus transformations; Quercus ilex